Torsional and cracking characteristics of steel fiber-reinforced oil palm shell lightweight concrete - Yap, Soon Poh; Alengaram, Ubagaram Johnson; Jumaat, Mohd Zamin; Khaw, K.R. (SAGE Publications (UK and US), 2016)
The study presents the investigations of the torsional behavior and crack resistance of a sustainable lightweight oil palm shell (OPS) concrete. In the comparison between the OPS concrete (OPSC) and normal weight concrete (NWC), the torsional failure of the NWC was sudden and brittle, while the OPSC exhibited post-cracking behavior. The second part of the study examines the effect of steel fibers of 0.25-1.00% in the OPSC to produce OPS fiber-reinforced concrete (OPSFRC). Improved mechanical properties and reduced brittleness were reported in the OPSFRC mixes. The addition of 1% steel fibers in the OPSC-100 mix produced the highest compressive and flexural strengths of 47 MPa and 8.2 MPa, respectively. The steel fibers up to 1% enhanced the ultimate torque, torsional toughness, and twist at failure of the OPSFRC specimens by 60%, 1000%, and 550%, respectively. The addition of steel fibers significantly improved the crack resistance of the OPSFRC specimens.